Tai Chi counteracts age-related somatosensation and postural control declines among older adults - Teng Zhang; Li Li; Jan M. Hondzinski; Min Mao; Wei Sun; Qipeng Song (Elsevier, 2024)
Objective: To investigate the effect of a 16-week Tai Chi practice on strength, tactile sensation, kinesthesia, and static postural control among older adults of different age groups. Methods: This is a quasi-experimental study. Thirteen participants aged 60-69 years (60-69yr), 11 aged 70-79 years (70-79yr), and 13 aged 80-89 years (80-89yr) completed 16 weeks of 24-form Tai Chi practice. Their ankle and hip peak torque, tactile sensation, ankle and knee kinesthesia, and the root mean square of the center of pressure (Cop-RMS) were measured before (week 0) and after (week 17) practice. Results: 80-89yr showed less ankle plantar/dorsiflexion and hip abduction peak torques (p = 0.003, p < 0.001, p = 0.001), and a greater ankle plantar/dorsiflexion kinesthesia (p < 0.001, p = 0.002) than 60-69yr and 70-79yr. Greater ankle plantar/dorsiflexion and hip abduction torques (p = 0.011, p < 0.001, p = 0.045), improved arch and heel tactile sensation (p = 0.040, p = 0.009), and lower knee flexion/extension kinesthesia (p < 0.001, p = 0.044) were observed at week 17. The significant group*practice interaction for the fifth metatarsal head tactile sensation (p = 0.027), ankle plantar/dorsiflexion kinesthesia (p < 0.001, p = 0.004), and the CoP-RMS in the mediolateral direction (p = 0.047) only in 80-89yr revealed greater improvement at week 17. Conclusion: Tai Chi practice increased strength, tactile sensation, kinesthesia, and static postural control among older adults. Tai Chi practice improved tactile, kinesthesia sensations, and static postural control among older adults over 80, who presented with worse strength and kinesthesia than their younger counterparts. Tai Chi practice offers a safe exercise option for those aged over 80 to encourage improvements in sensorimotor control.